Otomatisasi Sistem Inventarisasi Barang di Sekolah: Studi pada SD Negeri Sidorejo Lor 06, Salatiga - Anis Setia Wati; Ariya Dwika Cahyono; Evi Maria (AITI, 2020)
The purpose of this research is to automate the inventory system of goods in SD Sidorejo Lor 06 Salatiga by developing a web based inventory system. This research focuses on designing systems ranging from listing inventory data, logging incoming goods, logging outgoing goods, performing mutation of goods, and making inventory reports. This research develops a system using the Waterfall software development model. Inventory system of goods is developed by using CodeIgniter framework and MySQL as database. Additionally, the system has two user levels: admin and user. The features of this information system include managing the data of items such as adding, editing, deleting, printing and storing data on the dashboard menu, items, transactions, reports. Hence, the aim of the automation is to solve delays and inaccuracy problem of the inventory reports in SD Sidorejo Lor 06 Salatiga. The results of the inventory system testing developed in this research is proven to speed up the process of producing inventory reports. The inventory report creation process takes only 22.30 seconds. The system has also been shown to improve the accuracy of inventory reporting in school. The system notified if the input of the number of goods out exceeded the stock of the goods owned.